Evaluasi Pelatihan Dan Pengembangan Karyawan Dalam Meningkatkan Kinerja Tenaga Non Medis Di Rumah Sakit Umum Hermina Arcamanik - Rozi, Shafa Azmi Azizah; Ariyani, Nurul Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
To what extent can hospital non-medical personnel be improved by employee education and training? That is the question this research seeks to answer. Interviews with up to two HRD staff members from the ET&D department were conducted to gather data for this qualitative descriptive study. Systematic and planned additional training considerably increases workers' competency and motivation to work, according to the study's findings. Management buy-in and company culture are other factors that could make or break a growth initiative. The hospital administration hopes to use this data to design a better training program for non-medical employees.